1997
DOI: 10.1165/ajrcmb.17.5.2833
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor- β1 Is a Potent Inhibitor of Glutathione Synthesis in the Lung Epithelial Cell Line A549: Transcriptional Effect on the GSH Rate-limiting Enzyme γ -Glutamylcysteine Synthetase

Abstract: Glutathione (GSH) is an essential antioxidant tripeptide that protects mammalian cells against oxidants and xenobiotics. Patients with fibrotic lung disorders have very low levels of GSH in their alveolar epithelial lining fluid (ELF), whereas transforming growth factor (TGF)-beta is overexpressed in their alveolar epithelial cells. We observed that TGF-beta1 increased susceptibility of the human alveolar epithelial cell line A549 to H2O2-mediated cytotoxicity (P < 0.05), decreased the activities of the antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 45 publications
6
97
0
1
Order By: Relevance
“…While it has been reported that reduced levels of GSH in the epithelial lining fluid were found in asthmatic lungs compared with those in normal subjects [37], results on GSH levels in APC in asthmatic patients are not available to date. However, it is possible that the GSH levels in APC in the patients with asthma are decreased, since TGF-b1, which acts as a potent inhibitor of GSH synthesis [38], has been shown to be systemically elevated in asthmatic patients [39].…”
Section: P<001) These Results Suggest That Edc Might Exacerbate Airmentioning
confidence: 99%
“…While it has been reported that reduced levels of GSH in the epithelial lining fluid were found in asthmatic lungs compared with those in normal subjects [37], results on GSH levels in APC in asthmatic patients are not available to date. However, it is possible that the GSH levels in APC in the patients with asthma are decreased, since TGF-b1, which acts as a potent inhibitor of GSH synthesis [38], has been shown to be systemically elevated in asthmatic patients [39].…”
Section: P<001) These Results Suggest That Edc Might Exacerbate Airmentioning
confidence: 99%
“…TGF-b 1 , however, may not only interfere with the defence mechanisms of the epithelium of the lung by reducing SLPI levels. In a recent study ARSALANE et al [38] demonstrated that TGF-b 1 is able to inhibit glutathione synthesis in the human alveolar epithelial cell line A549. Glutathione is the most important extracellular antioxidant of the human lung [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown increased expression of TGF-b1 in bronchiolar and alveolar epithelium in IPF and COPD patients, and higher levels in the BALF of atopic asthmatics as compared to healthy subjects [154,155]. TGF-b1 also downregulates c-GCS-HS mRNA and glutathione synthesis in human alveolar epithelial cells and pulmonary artery endothelial cells in vitro [109,110]. Interestingly, recent studies by FACTOR et al [156] showed decreased glutathione synthesis in a TGF transgenic (overexpression) mouse model and increased susceptibility to oxidant-mediated injury.…”
Section: Effect Of Growth Factorsmentioning
confidence: 99%